Influence of organic waste and growing media on seed germination and seedling growth of Papaya (Carica papaya L.) under polyhouse conditions - Mahendra Choudhary; Anuj Kumar (Annals of Agricultural Research, 2025)
A field experiment was conducted to study the “Effect of organic wastes and growing media on seed germination and seedling growth of papaya (Carica papaya L.) under polyhouse condition” was taken up at the instructional farm of Department of Horticulture, College of Agriculture, Rewa (M.P.) during October to November 2022. There were thirteen treatments combinations of organic wastes and growing media viz. T1- Control, T2- Cow dung 12 hours + Soil + FYM + Vermicompost T3- Cow dung 12 hours + Soil + FYM + Cocopeat T4- Cow dung 24 hours + Soil + FYM + Vermicompost T5- Cow dung 24 hours + Soil + FYM + Cocopeat T6- Cow dung slurry 12 hours + FYM + Vermicompost T7- Cow dung slurry 12 hours +Soil + FYM + Cocopeat T8- Cow dung slurry 24 hours + Soil + FYM + Vermicompost T9- Cow dung slurry 24 hours + Soil + FYM + Cocopeat T10- Cow urine 12 hours + Soil + FYM + Vermicompost T11- Cow urine 12 hours + Soil + FYM + Cocopeat T12- Cow urine 24 hours + Soil + FYM + Vermicompost T13- Cow urine 24 hours + Soil + FYM + Cocopeat. Which were laid out in randomized block design with three replications.